Perbandingan Hasil Belajar Mahasiswa dan Guru yang Menggunakan Kurikulum Berbasis Nilai Filosofi John Dewey dan Kurikulum Tradisional - Ade Reza Maulana; Desty Endrawati Subroto; Yesi Oktaviana; Friska Maudina Zamri; Nazwa Zahra Tirtana (PT. Penerbit Tiga Mutiara, 2025)
This study aims to compare the effectiveness of a curriculum based on John Dewey's philosophical values with a traditional curriculum in improving student learning outcomes in higher education. Traditional curricula often focus on a hierarchy of subjects and rote learning, which tend to neglect concrete experiences, social relevance, and interdisciplinary connections. In contrast, Dewey's educational philosophy emphasizes a student-centered approach, democracy in education, authentic learning experiences, and multidisciplinary problem-solving. Dewey criticized the rigidity of traditional curricula for being inflexible and unresponsive to individual needs. As an alternative, he proposed a dynamic education approach oriented toward real-life experiences, aiming to prepare students for democratic life through the development of critical thinking and social skills. Further research is needed to evaluate the effectiveness of this approach in enhancing learning outcomes and fostering personal development in students. However, implementing approaches based on Dewey's philosophical values, such as Outcome-Based Education (OBE) and Student-Centered Learning (SCL), faces significant challenges. Barriers such as content-based curricula, unsupportive teaching policies, insufficient infrastructure, limited facilities, and high faculty workloads remain major obstacles, as found in the context of education in Afghanistan. This highlights the need for educational reform that focuses not only on curriculum development but also on strengthening infrastructure, policies, and operational support.